2018
DOI: 10.1038/s41467-018-05630-6
|View full text |Cite
|
Sign up to set email alerts
|

N2 activation on a molybdenum–titanium–sulfur cluster

Abstract: The FeMo-cofactor of nitrogenase, a metal–sulfur cluster that contains eight transition metals, promotes the conversion of dinitrogen into ammonia when stored in the protein. Although various metal–sulfur clusters have been synthesized over the past decades, their use in the activation of N2 has remained challenging, and even the FeMo-cofactor extracted from nitrogenase is not able to reduce N2. Herein, we report the activation of N2 by a metal–sulfur cluster that contains molybdenum and titanium. An N2 moiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 43 publications
0
62
0
Order By: Relevance
“…In our recent study, the cubane‐type [Mo 3 S 4 Ti] cluster Cp* 3 Mo 3 S 4 TiCl 2 ( 2 ) was synthesized from the cluster anion [Cp* 3 Mo 3 S 4 ] − [ 1 ] − , which was generated in situ by treatment of the neutral cluster Cp* 3 Mo 3 S 4 ( 1 ) with 1 equivalent of sodium naphthalenide in THF. In this study, the cluster anion was successfully isolated in 56 % yield as dark‐green crystals of [K(18‐crown‐6)][ 1 ] − , from the reaction of 1 with equimolar amounts of 18‐crown‐6 and KC 8 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our recent study, the cubane‐type [Mo 3 S 4 Ti] cluster Cp* 3 Mo 3 S 4 TiCl 2 ( 2 ) was synthesized from the cluster anion [Cp* 3 Mo 3 S 4 ] − [ 1 ] − , which was generated in situ by treatment of the neutral cluster Cp* 3 Mo 3 S 4 ( 1 ) with 1 equivalent of sodium naphthalenide in THF. In this study, the cluster anion was successfully isolated in 56 % yield as dark‐green crystals of [K(18‐crown‐6)][ 1 ] − , from the reaction of 1 with equimolar amounts of 18‐crown‐6 and KC 8 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…As a wide range of metals are compatible with the anionic [Cp* 3 Mo 3 S 4 ] − platform, one can apply the present synthetic protocol for [Mo 3 S 4 M] cubes to various second‐ and third‐row transition metals to generate a number of prospective catalysts for homogeneous reactions, even though the cationic [Cp* 3 Mo 3 S 4 ] + platform is already able to accommodate some late transition metals from the second‐row such as Ru and Pd . Recent studies have demonstrated the potential of cubic metal‐sulfur clusters for the activation of small molecules, and therefore, such [Mo 3 S 4 M] cubes can potentially be employed in the stoichiometric/catalytic reduction of N 2 , CO 2 , or CO. Research in this direction is currently in progress in our group, and the results will be reported in due course. One could possibly also apply the present [Mo 3 S 4 M] cubes as catalyst precursors to various homogeneous processes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Learning from the nature, the biological nitrogen fixation can give the researchers some inspiration to design ideal catalysts to accelerate the NRR process. And according to the component elements of nitrogenases, the Mo and S elements play significant roles in NRR . Recently, transitional metal dichalcogenides (TMDs) have received much attention in the catalytic field due to their inherent advantages (2D structure, adjustable bandgap, and so on) for various reaction, such as CO 2 electroreduction and HER .…”
Section: Defect Engineering Strategies For Nrrmentioning
confidence: 99%